(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To evaluate the feasibility, safety and efficacy of one-shot dilation (OSD) in standard percutaneous nephrolithotomy (PCNL). Methods: This is a prospective, single -center study conducted between January 2017 to June 2019. Patients who underwent PCNL using one shot dilatation (21 – 24 Fr) for access in PCNL were included in the study. Access time, fluoroscopy time, successful dilation time, stone free rate, decrease hemoglobin level and transfusion rate, complication rate, length of post operative hospital stay, cost were recorded. Data was analyzed and reported using summary statistics. Results: A total of 30 patients were enrolled in this survey. 30 patients in one shot dilation (OSD) group.The mean age was 39.5 years. Control group of 30 patients were included in standard PCNL procedure where method of tract dilation was done by regid Amplatz dilators. Access time and fluoroscopy time in OSD group was approximately shorter. Statistically it was significant. Successful dilation and stone free rate were subsequently 98% and was significant. Data collected included patient access time, radiation exposure, total operating time, preoperative and postoperative hemoglobin concentrations, tract dilatation failures, complications and transfusions. Conclusion: The use of one shot and standard prone position under general anaesthesia combines the advantages of these both methods including less radiation exposure and shorter access and operative time. One shot dilation technique is safe, economical and feasible technique with added advantage,lesser radiation exposure and lesser chance of blood transfusion. Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.114-117